The effect of link peptide on proteoglycan synthesis in equine articular cartilage - Dean, M.F.; Lee, Y.W.; Dastjerdi, A.M.; Lees, P. (Biochimica et biophysica acta, 2003)
The basal rate of in vitro proteoglycan (PG) synthesis in explants of equine articular cartilage was subject to considerable variation in animals of the same age but was greater in younger than older animals. Synthesis of PGs in explant cultures was stimulated by a synthetic link peptide, identical in sequence to the N-terminus of the link protein (LP) of PG aggregates, in a similar manner to that demonstrated previously for human articular cartilage [Biochem. Soc. Trans. 25 (1997) 427; Arthritis Rheum. 41 (1998) 157]. Stimulation occurred in tissue from animals ranging from 1 to 30 years old but older animals required higher concentrations of peptide to produce a measurable response. Synthesis of PGs increased in a concentration-dependent manner and was paralleled by increases in the ability of aggrecan monomers to form aggregates with hyaluronan (HA). In addition to its effect on synthesis of PGs, link peptide also increased synthesis of both aggrecan and LP mRNA. Cartilage explant and chondrocyte cultures secreted small amounts of biologically active interleukin 1 (IL 1) and secretion of this cytokine was reduced considerably by the addition of link peptide. Reduction in the activity of this catabolic cytokine coupled with the increased synthesis of mRNA for aggrecan and link peptide may be the mechanism by which link peptide exerts its positive effect on the rate of PG synthesis in articular cartilage.